THEMIS observations of ULF wave excitation in the nightside plasma sheet during sudden impulse events. Issue 1 (24th January 2013) - Shi, Q. Q.; Hartinger, M.; Angelopoulos, V.; Zong, Q.‐G.; Zhou, X.‐Z.; Zhou, X.‐Y.; Kellerman, A.; Tian, A. M.; Weygand, J.; Fu, S. Y.; Pu, Z. Y.; Raeder, J.; et al.
Abstract : [1] Sudden impulses (SIs) are an important source of ultra low frequency (ULF) wave activity throughout the Earth's magnetosphere. Most SI‐induced ULF wave events have been reported in the dayside magnetosphere; it is not clear when and how SIs drive ULF wave activity in the nightside plasma sheet. We examined the ULF response of the nightside plasma sheet to SIs using an ensemble of 13 SI events observed by THEMIS (Timed History of Events and Macroscale Interactions during Substorms) satellites (probes). Only three of these events resulted in ULF wave activity. The periods of the waves are found to be 3.3, 6.0, and 7.6 min. East‐west magnetic and radial electric field perturbations, which typically indicate the toroidal mode, are found to be stronger and can have phase relationships consistent with standing waves. Our results suggest that the two largest‐amplitude ULF responses to SIs in the nightside plasma sheet are tailward‐moving vortices, which have previously been reported, and the dynamic response of cross‐tail currents in the magnetotail to maintain force balance with the solar wind, which has not previously been reported as a ULF wave driver. Both mechanisms could potentially drive standing Alfvén waves (toroidal modes) observed via the field‐line resonance mechanism. Furthermore, both involve frequency selection and a preference for certain driving conditions that can explain the small number of ULF wave events associated with SIs in the nightside plasma sheet. Key Points: In 3 of 13 SI events, steady ULF wave is induced in the nightside plasma sheet Field perturbations are usually consistent with standing toroidal Alfven waves Tailward moving vortices or dynamic response of tail currents may explain